Species-specific Inflammatory Responses as a Primary Component for the Development of Glomerular Lesions in Mice and Monkeys Following Chronic Administration of a Second-generation Antisense Oligonucleotide. (July 2014) - Frazier, Kendall S.; Sobry, Cécile; Derr, Victoria; Adams, Mike J.; Besten, Cathaline Den; Kimpe, Sjef De; Francis, Ian; Gales, Tracy L.; Haworth, Richard; Maguire, Shaun R.; Mirabile, Rosanna C.; Mullins, David; et al.
Chronic administration of drisapersen, a 2′-OMe phosphorothioate antisense oligonucleotide (AON) to mice and monkeys resulted in renal tubular accumulation, with secondary tubular degeneration. Glomerulopathy occurred in both species with species-specific characteristics. Glomerular lesions in mice were characterized by progressive hyaline matrix accumulation, accompanied by the presence of renal amyloid and with subsequent papillary necrosis. Early changes involved glomerular endothelial hypertrophy and degeneration, but the chronic glomerular amyloid and hyaline alterations in mice appeared to be species specific. An immune-mediated mechanism for the glomerular lesions in mice was supported by early inflammatory changes including increased expression of inflammatory cytokines and other immunomodulatory genes within the renal cortex, increased stimulation of CD68 protein, and systemic elevation of monocyte chemotactic protein 1. In contrast, kidneys from monkeys given drisapersen chronically showed less severe glomerular changes characterized by increased mesangial and inflammatory cells, endothelial cell hypertrophy, and subepithelial and membranous electron-dense deposits, with ultrastructural and immunohistochemical characteristics of complement and complement-related fragments. Lesions in monkeys resembled typical features of C3 glomerulopathy, a condition described in man and experimental animals to be linked to dysregulation of the alternative complement pathway. Thus, inflammatory/immune mechanisms appear critical to glomerular injury with species-specific sensitivities for mouse and monkey. The lower observed proinflammatory activity in humans as compared to mice and monkeys may reflect a lower risk of glomerular injury in patients receiving AON therapy.